Environmental and occupational exposure assessment - Nogueira, Ana (2018)
Introduction: Environmental and Occupational Exposure Assessment: a) Indoor Environmental Quality (Office buildings, schools, waiting rooms – tasks developed do not involve/ required manipulation of chemical or biological agents, nor exposure to physical agents); b) Occupational Exposure (Factories, healthcare services, laboratories, wastewater treatment plants,… - intentional exposure due to developed tasks).